OBSTACLES IN CHILD REMOVAL FROM UNSAFE FAMILY ENVIRONMENTS: A COMPREHENSIVE STUDY OF FRONTLINE PROFESSIONALS OF CHILD PROTECTION & WELFARE BUREAU, PUNJAB-PAKISTAN - Ehtsham Arshad (International Journal of Contemporary Issues in Social Sciences, 2023)
Objective: This article analyzes the challenges faces by frontline child protection workers when they encounter a family situation and need to determine whether the child should be removed from an unsafe environment or not. It is important to identify these obstacles in order to minimize the negative consequences that arise from the unnecessary removal of children from their family environments. Maltreatment with children often occurs in family environments in presence of various other problems and it becomes unavoidable for the professionals to remove children from such families. Methods: The present gender-neutral study, based in Lahore, aims to address the challenges faced by professionals through an in-depth analysis of the existing patterns of child protection in Punjab. The research design was qualitative combining semi-structured in-depth interviews and a focus group discussions (FGDs). The sample size (n=13) was comprised of experienced (> 05 years) frontline professionals of Child Protection and Welfare Bureau (CP&WB), Punjab. Based on thematic analysis of data, various challenges encountered by professionals have been identified. Results: The removal of children from unsafe family environments in Pakistan is hindered by societal beliefs and cultural practices that stigmatize and discriminate against reporting child abuse cases. Additionally, weak legal frameworks, limited resources and bureaucratic hurdles make it difficult for professionals to remove children from unsafe environments. Socioeconomic factors such as lack of education, poverty, and limited resources also contribute to the challenges faced in removing children, while lack of alternative care options and inter-agency coordination further complicates the process. The implementation of special laws related to children is challenging due to a lack of awareness and education on child protection issues. Lastly, the psychological and emotional impact must be considered during the removal in order to ensure the well-being of both the child and the family, as well as the employee oneself. Conclusion: It is concluded in study that the separation of children from parents should be the extremist act by professionals. Such cases should be dealt with extreme care, and thus training should be an integral part of professionals’ jobs. Thus, study proposes recommendations for policymakers, lawmakers and child protection professionals to ensure a better future of children in need.